2018
DOI: 10.3390/ph11010017
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Epilepsy and Plasticity

Abstract: Undoubtedly, one of the most interesting topics in the field of neuroscience is the ability of the central nervous system to respond to different stimuli (normal or pathological) by modifying its structure and function, either transiently or permanently, by generating neural cells and new connections in a process known as neuroplasticity. According to the large amount of evidence reported in the literature, many stimuli, such as environmental pressures, changes in the internal dynamic steady state of the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 175 publications
0
36
0
Order By: Relevance
“…The filopodia-like spines are presumably prone to support initiation of synaptic plasticity processes [4, 36, 50]. Therefore, this result may suggest that DG may undergo synaptic plasticity that may predispose this brain structure to support epileptogenesis that is a frequent consequence of TBI [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…The filopodia-like spines are presumably prone to support initiation of synaptic plasticity processes [4, 36, 50]. Therefore, this result may suggest that DG may undergo synaptic plasticity that may predispose this brain structure to support epileptogenesis that is a frequent consequence of TBI [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, since PNNs are thought to inhibit synaptic plasticity [14, 17], the decrease in PV-positive neurons not surrounded by PNNs observed in this study indicates a decrease in plasticity in the hippocampus of mice after kindling acquisition. It has long been known that changes to synaptic plasticity are associated with epileptogenesis [6, 7]. For instance, neural circuits that maintain high excitability are caused by changes in synaptic plasticity due to repetitive stimulation in patients with epilepsy and experimental animal models of epilepsy [6062].…”
Section: Discussionmentioning
confidence: 99%
“…Although seizures can induce neuronal death, they also have nonfatal pathophysiological effects on neuronal structure and function [5]. For example, epileptogenesis is associated with changes to synaptic plasticity [6, 7]. However, what causes and maintains these changes has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms underlying kindling and the development of abnormal excitability in epilepsy are poorly understood. Studies have shown that changes in synaptic plasticity lead to epilepsy ( Scharfman et al, 2002 ; Jarero-Basulto JJ et al, 2018 ). We have shown in previous studies that activation of astrocytes in the PTZ-induced kindling model may lead to increased ECM secretion ( Ueno et al, 2019a , 2019b ).…”
Section: Introductionmentioning
confidence: 99%